Kepastian Hukum Jaminan Fidusia atas Cryptocurrency Sebagai Aset Digital Tidak Berwujud dalam Perjanjian Kredit di Indonesia - Putri, Lisa Angelie; Tarina, Dwi Desi Yayi (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The development of information technology and digitalization has encouraged the emergence of cryptocurrency as a digital asset that attracts attention throughout the world, including in Indonesia. However, legal regulations related to cryptocurrency, especially in the context of fiduciary guarantees, are still very minimal. This study aims to explore the legal certainty of fiduciary guarantees for cryptocurrency as intangible digital assets in credit agreements in Indonesia. The research method used is normative juridical, which focuses on the analysis of existing laws and regulations, legal documents, and related literature. The results of the study show that if cryptocurrency is used as collateral for debt, ownership of the cryptocurrency will be transferred to the institution that handles the guarantee. The authorities will issue a document showing who the owner is. A fiduciary institution is the right choice to handle this, because the nature of the crypto object is recorded in the document, not in physical form. However, due to the high fluctuation in cryptocurrency prices, collateral institutions tend to be reluctant to accept crypto as collateral. As a result, creditors or institutions receiving collateral are reluctant to take risks related to fluctuations in the value of crypto. Cryptocurrency users are at risk of capital losses, such as buying at a price higher than the selling price, or losing other assets if there is an error in purchasing crypto.